2021
DOI: 10.3389/fpsyg.2021.655410
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Loneliness and Psychological Adjustment: Validation of the Italian Version of the Interpersonal Acceptance–Rejection Loneliness Scale

Abstract: In recent literature, many researchers have highlighted that the feeling of loneliness can be considered a sign of relevant distress with short- and long-term consequences on the health of people who needs to be appropriately monitored and treated. In this view, the Interpersonal Acceptance–Rejection Loneliness Scale (IPARLS) has been developed to evaluate the subjective feelings and distress related to interpersonal loneliness and to overcome the limits of the previous scales; however, its psychometric charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…This result can be read as a higher vulnerability to showing psychological problems under conditions of high isolation or loneliness in men. This result is in line with recent literature confirming men's greater sensitivity to loneliness (Barreto et al, 2021;Maes et al, 2019;Senese et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This result can be read as a higher vulnerability to showing psychological problems under conditions of high isolation or loneliness in men. This result is in line with recent literature confirming men's greater sensitivity to loneliness (Barreto et al, 2021;Maes et al, 2019;Senese et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…At this regard, it is interesting to point out that few studies in the literature have investigated sex differences in both components of isolation highlighting the importance of considering this variable. For example, it has been shown that men are most vulnerable to loneliness (Barreto et al, 2021), that sex moderates the association between age and loneliness (Senese et al, 2021) and that sex differences were moderated by age, sampling area and year of publication (Maes et al, 2019).…”
mentioning
confidence: 99%
See 3 more Smart Citations